Symphonies, Part 1 The Salisbury and Canterbury Symphonies (1778-1784); Part 2 - Horton, Peter (Oxford University Press, Oxford, 2005)
RESUMEN: Ed. Ian Graham-Jones. Recent Researches in the Music of the Classical Era, 62-3. (A-R Editions, Middleton, Wis., 2001)